**Introduction for equations with variables on both sides calculator:**

Equation with variable are the important part of algebra, generally the equation with same variable are said to be equation with variables on both sides. Fro example x+2x+4 = x+8 here x is the variable in this equation we need to find the value of variable using calculator. In this article we will discuss about equation with variables on both sides calculator with suitable example problem.

**Equations with variables on both sides calculator:**

Related Calculators | |

Solving Equations with Variables on both Sides Calculator | Variable Equation Calculator |

Linear Equations in Two Variables Calculator | Variable Equation Solver |

**Simplify the following equations with variables on both sides calculator**

**Problem(i) : The equation is 2x+4 = 4x+6+8.**

**Solution**

The given equation is 2x+4 = 4x+6+8.

**Step 1: **In this given equation collect the variable

2x-4x+4 = 6+8

**Step2:** Collecting the constant

2x-4x+4 = 14

2x-4x = 14-4.

**Step 3: **simplifying the equation

-2x = 10

**Step 4:** Dividing both sides by -2

`(-2x)/-2` =`10/-2`

x= -5

**Step 5:** The variable of x is -5.

**Problem(ii) : The equation is 3x= 4x+6+1.**

**Solution**

The given equation is 3x = 4x+6+1.

**Step 1:** In this given equation collect the variable

3x-4x = 6+1

**Step 2: **Collecting the constant

3x-4x = 7

3x-4x = 7.

**Step 3: **simplifying the equation

-x = 7

**Step 4: **The variable of x is -7.

**Simplify the following equations with variables on both sides calculator**

**Problem (i) The equation is -5x+7+8 = -9x +15+10**

**Solution**

The given equation is -5x+7+8 = -9x +15+10

**Step 1: **In this given equation collect the variable

-5x+9x+15 = 15+10

**Step2:** Collecting the constant

-5x+9x+15 = 25

-5x+9x = 25-15.

**Step 3: **simplifying the equation

4x = 10

**Step 4: **Dividing both sides by 4

`(4x)/4` = `10/4`

x = `5/2`

**Step 5: **The variable of x is `5/2` .

**Problem (ii) The equation is -2x+7+13 = 4x +14**

**Solution**

The given equation is -2x+7+13 = 4x +14

**Step 1:** In this given equation collect the variable

-2x-4x+7+13 = 14

**Step2: **Collecting the constant

-2x-4x+20 = 14

-6x = 14-20

**Step 3:** simplifying the equation

-6x = -6

**Step 4:** Dividing both sides by -6

`(-6x)/-6` =`(-6)/(-6)`

x = 1

**Step 5:** The variable of x is 1.